In vitro and in vivo characterization of domperidone-loaded fast dissolving buccal films - Gamal M. Zayed; Saleh Abd-El Rasoul; Mohamed A. Ibrahim; Mohammed S. Saddik; Doaa H. Alshora (Elsevier, 2020)
The delivery of drugs via fast dissolving films is an effective alternative for drugs with low bioavailability when administered by other routes. This is the case of domperidone (DMP) an anti-emetic drug with low water solubility and vulnerable to extensive first-pass effect. To overcome these limitations, in this work, we designed and produced fast dissolving muco-adhesive buccal films of domperidone using varying amount polyvinylpyrrolidone (PVP K-90) using the solvent casting method. Films loaded with more than 10% of drug were not homogenous and opaque as indicated by white patches of drug in the film matrix. Formulation of DMP in the film form resulted in conversion of the drug from crystalline state to the semi-crystalline state as indicated by X-ray powder diffraction analysis. Moreover, about 40% of drug loaded within the films was released during the first five minutes compared to only about only 6.5% of pure drug in drug dissolution assays in vitro. In vivo pharmacokinetics analysis revealed that the DMP-loaded film had higher maximum plasma concentration (Cmax) and shorter time to reach Cmax (Tmax) than a commercially available tablet formulation. In conclusion, the produced DMP buccal film formulation showed high absorption rate, rapid onset of action, and improved bioavailability compared with the conventional tablet. Our findings may support the development of novel dosage forms for the transmucosal delivery of DMP for convenient, rapid, and effective treatment of nausea and vomiting. Keywords: Domperidone, Buccal films, Polyvinylpyrrolidone, Bioavailability, Pharmacokinetics